Is There a Rendezvous for SARS-CoV-2 and Agmatine - Kotagale, Nandkishor; Taksande, Brijesh; Inamdar, Nazma (Coronaviruses, 2022)
The catastrophe of the ongoing COVID-19 pandemic is caused by Severe Acute Respiratory Syndrome Corona Virus-2 (SARS-CoV-2). The respiratory system appears to be ground zero in the majority of the patients. However, many other organs can get infected by cytokines, chemokines and other mediators released in response to the presence of the virus. The neurotropism by the SARS-CoV-2 is established beyond doubt. In addition to non-specific symptoms, the symptoms specific to central and/or peripheral nervous system diseases as well as neuromuscular diseases have been observed in numerous clinical cases. These observations and the experiences with other coronavirus infections earlier and flu pandemics raise concerns not only about the neurological effects in active disease but also about the long-term effects generated by the infection, immune and inflammatory functions. The knowledge of biological actions of agmatine in the backdrop of physiological events instigated by invading SARS-CoV-2 and host’s response, especially in neural events, focuses on the possible overlaps of biomolecular pathways at a number of instances. This is not surprising since the factors stimulated during SARS-CoV-2 infection are the disease- generating neuroinflammatory components altered by agmatine. Hence, we hypothesize the possible beneficial role of agmatine in SARS-CoV-2 infection. Based on a narrative review of the literature, agmatine can be proposed as a plausible beneficial candidate for supporting treatment of SARS-CoV-2 infection and for addressing post-infection neurological complications.
Keywords: COVID-19